The power of the cities and the power in the cities: a multiscale perspective from Portugal - José Alberto Rio Fernandes; Filipe Teles; Pedro Chamusca; João Seixas (Boletín de la Asociación de Geógrafos Españoles)
Cities –or the urban complex spaces that they are becoming– are vital in society’s future, particularly in a general context of globalization. In this setting, power fragmentation and government to governance transitions, which are indisputable and significant phenomena, go hand in hand with urban movements that are becoming increasingly relevant, both through their direct action, and as a consequence of democratic responsibility. In Portugal, however, urban movements and civic associations in general seem rather discreet in their activities, dimension and role. In fact, there is no strong evidence that the 2008–2014 crisis has brought any dramatic change in these aspects. In this article we aim to shed some light on plausible explanations for this apparent inertia. Signs of change, in a context of increased governance and new urban dynamics do exist but do not seem to follow the trend that is thriving in several cities on other European countries. In face of new opportunities for a multiscalar approach to politics, planning and action, after centuries of a (still) dominant hierarchical and sectorial approach, we examine the context of the power of the cities and in the cities in Portugal.